Electrically Induced Mixed Valence Increases the Conductivity of Copper Helical Metallopolymers - Emrys Evans (Advanced Materials, 2021)
Controlling the flow of electrical current at the nanoscale typically requires complex top-down approaches. Here, a bottom-up approach is employed to demonstrate resistive switching within molecular wires that consist of double-helical metallopolymers and are constructed by self-assembly. When the material is exposed to an electric field, it is determined that ≈25% of the copper atoms oxidize from CuI to CuII, without rupture of the polymer chain. The ability to sustain such a high level of oxidation is unprecedented in a copper-based molecule: it is made possible here by the double helix compressing in order to satisfy the new coordination geometry required by CuII. This mixed-valence structure exhibits a 104-fold increase in conductivity, which is projected to last on the order of years. The increase in conductivity is explained as being promoted by the creation, upon oxidation, of partly filled d2 orbitals aligned along the mixed-valence copper array; the long-lasting nature of the change in conductivity is due to the structural rearrangement of the double-helix, which poses an energetic barrier to re-reduction. This work establishes helical metallopolymers as a new platform for controlling currents at the nanoscale.